Human Resource Management in Public Administration: The Ongoing Tension Between Reform Requirements and Resistance to Change - Branka Zolak Poljašević; Ana Marija Gričnik; Simona Šarotar Žižek (Administrative Sciences)
Human resource management (HRM) plays a critical role in shaping public administration by ensuring the efficiency, effectiveness, and adaptability of public institutions. In post-socialist European countries, HRM reforms have been central to broader public sector transformations aimed at increasing transparency, meritocracy, and efficiency. However, these reform processes are often hindered by institutional inertia, political influences, and resistance to change. This study examines how reform requirements and resistance to change influence the transformation of HRM practices in public administration across post-socialist European countries. Using a structured literature review approach, this study systematically analyzes peer-reviewed academic research published in quality journals indexed in the Web of Science database. A purposive and criterion-based sampling strategy was applied to select relevant studies that address HRM reforms, institutional challenges, and governance dynamics within the post-socialist context. Findings indicate that historical legacies, politicization, and institutional resistance remain significant barriers to the successful implementation of HRM reforms. This study also highlights that while legal and procedural adjustments have been made, many public administrations struggle with the practical application of reform policies due to entrenched bureaucratic cultures and limited professionalization of HRM functions. By providing a structured synthesis of existing research, this study contributes to a deeper understanding of HRM transformation in post-socialist public administrations. It also identifies areas wherein further empirical research is needed to explore potential strategies for overcoming barriers to reform.